Inhibition of Myc transcriptional activity by a mini‐protein based upon Mxd1. Issue 10 (11th March 2020) - Demma, Mark J.; Hohn, Michael J.; Sun, Angie; Mapelli, Claudio; Hall, Brian; Walji, Abbas; O'Neil, Jennifer
Abstract : Myc, a transcription factor with oncogenic activity, is upregulated by amplification, translocation, and mutation of the cellular pathways that regulate its stability. Inhibition of the Myc oncogene by various modalities has had limited success. One Myc inhibitor, Omomyc, has limited cellular and in vivo activity. Here, we report a mini‐protein, referred to as Mad, which is derived from the cellular Myc antagonist Mxd1. Mad localizes to the nucleus in cells and is 10‐fold more potent than Omomyc in inhibiting Myc‐driven cell proliferation. Similar to Mxd1, Mad also interacts with Max, the binding partner of Myc, and with the nucleolar upstream binding factor. Mad binds to E‐Box DNA in the promoters of Myc target genes and represses Myc‐mediated transcription to a greater extent than Omomyc. Overall, Mad appears to be more potent than Omomyc both in vitro and in cells. Abstract :